Identification of a novel mechanism of action of bovine IgG antibodies specific for Staphylococcus aureus - Furukawa, Mutsumi; Yoneyama, Hiroshi; Hata, Eiji; Iwano, Hidetomo; Higuchi, Hidetoshi; Ando, Tasuke; Sato, Mika; Hayashi, Tomohito; Kiku, Yoshio; Nagasawa, Yuya; Niimi, Kanae; Usami, Katsuki; et al. (Veterinary research (Paris), 2018)
Staphylococcus aureus is a major pathogen that causes subclinical mastitis associated with huge economic losses to the dairy industry. A few vaccines for bovine mastitis are available, and they are expected to induce the production of S. aureus-specific antibodies that prevent bacterial adherence to host cells or promote opsonization by phagocytes. However, the efficacy of such vaccines are still under debate; therefore, further research focusing on improving the current vaccines by seeking additional mechanisms of action is required to reduce economic losses due to mastitis in the dairy industry. Here, we generated S. aureus-specific bovine IgG antibodies (anti-S. aureus) that directly inhibited bacterial growth in vitro. Inhibition depended on specificity for anti-S. aureus, not the interaction between Protein A and the fragment crystallizable region of the IgG antibodies or bacterial agglutination. An in vitro culture study using S. aureus strain JE2 and its deletion mutant JE2ΔSrtA, which lacks the gene encoding sortase A, revealed that the effect of anti-S. aureus was sortase-A-independent. Sortase A is involved in the synthesis of cell-wall-associated proteins. Thus, other surface molecules, such as membrane proteins, cell surface polysaccharides, or both, may trigger the inhibition of bacterial growth by anti-S. aureus. Together, our findings contribute insights into developing new strategies to further improve the available mastitis vaccine by designing a novel antigen on the surface of S. aureus to induce inhibitory signals that prevent bacterial growth.